1997
DOI: 10.1115/1.2824189
|View full text |Cite
|
Sign up to set email alerts
|

Observation, Prediction, and Correlation of Geometric Shape Evolution Induced by Non-Isothermal Sintering of Polymer Powder

Abstract: Sintering of powders occurs in a wide array of manufacturing technologies and geophysical phenomena. Despite the prevalence of powder sintering, little attention has been paid to sintering of macroscopic shapes under non-isothermal conditions. In this paper (1) features of a representative, experimentally grown solid shape produced by non-isothermal sintering are discussed, (2) prediction of the solid shape evolution is achieved using a hybrid heat transfer, sintering, and consolidation model, (3) comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Equation 9 shows that for heterogeneous nucleation to proceed, the critical radius of the nucleus r* depends on the solid-liquid interfacial free energy c SL . In SLS, the solid and liquid are of nearly the same composition (assuming negligible contamination or segregation).…”
Section: Epitaxial Solidification In Slsmentioning
confidence: 99%
“…Equation 9 shows that for heterogeneous nucleation to proceed, the critical radius of the nucleus r* depends on the solid-liquid interfacial free energy c SL . In SLS, the solid and liquid are of nearly the same composition (assuming negligible contamination or segregation).…”
Section: Epitaxial Solidification In Slsmentioning
confidence: 99%
“…Their work was extended to three-dimensional parts and two-component metal powders by Zhang and co-workers [8][9][10][11][12][13], taking into account fluid flow caused by capillary and gravity forces through Darcy's law [8] or through the NavierStokes equations [13], investigating the effect of the powder layer thickness [9] and of the substrate [12], studying partial shrinkage [11]. The group of Childs developed a finite-element model for SLS/SLM using a similar viscous sintering law as Kandis and Bergman [6] to study the behavior of amorphous polymer powders [14], crystalline and glassfilled crystalline polymer powders [15], and stainless and tool steel powders [16]. Gusarov and co-workers studied in detail the phenomena related to the radiative heat transfer in powders and the interaction with the substrate.…”
Section: Introductionmentioning
confidence: 97%
“…In what follows, we briefly discuss an illustrative selection. Kandis, Bergman and co-workers [6,7] used a constitutive relation based on experimental measurements to account for the density change caused by sintering in SLS, and compared their simulations on polymer powders with experimentally produced parts. Their work was extended to three-dimensional parts and two-component metal powders by Zhang and co-workers [8][9][10][11][12][13], taking into account fluid flow caused by capillary and gravity forces through Darcy's law [8] or through the NavierStokes equations [13], investigating the effect of the powder layer thickness [9] and of the substrate [12], studying partial shrinkage [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all of these improvements, there are still very few modelling or experimental studies on micro‐scale coalescence that consider non‐isothermal conditions . This is because the spatial temperature distribution inside the particles/droplets was always neglected during the bridge formation due to their small size and, consequently, small Bi numbers ( Bi = hL/k ; where h is convection heat transfer coefficient of the surroundings, k is the conduction heat transfer coefficient of the body, and L is a characteristic length in the system, e.g., radius of the spheres) …”
Section: Introductionmentioning
confidence: 99%
“…However, several numerical and experimental studies demonstrated the importance of the influence of temperature on the coalescence rate in larger scales . By combining the micro‐scale model of Pokluda with the macro‐scale heat conduction equation, Tarafdar and Bergman investigated the non‐isothermal sintering of a series of amorphous polycarbonate particles under a temperature gradient.…”
Section: Introductionmentioning
confidence: 99%